(untitled) (Third Sector Social Economic Review, 2024)
This paper investigates the role of environmental policy stringency (EPSI) and its causal determinants in climate change mitigation across EU countries from 2000 to 2021. Using a panel quantile regression model, we analyze the effects of key variables such as CO2 emissions, foreign direct investment, and economic expansion, green technology diffusion on climate change mitigation efforts. Our findings reveal significant heterogeneity in the impact of these factors across different quantiles, with EPSI showing a stronger positive influence on climate change mitigation at higher levels of mitigation outcomes. Economic growth, green technology diffusion, and foreign direct investment exhibit nonlinear effects, while CO2 emissions play a more critical role in contexts with higher mitigation outcomes. The presence of long-term cointegration between climate change mitigation, EPSI, and these determinants, as well as Granger causality, underscores the need for integrated, adaptive policy strategies. Furthermore, the findings indicate a sustained relationship between climate change mitigation and EPSI, underscoring the importance for policymakers to scrutinize measures and strategies aimed at fostering the development of green technologies and energy sources to effectively address climate change.